Exclusive inhibition of IL-6 trans-signaling by soluble gp130FlyRFc. Issue 4 (December 2021) - Berg, Anna F.; Ettich, Julia; Weitz, Hendrik T.; Krusche, Matthias; Floss, Doreen M.; Scheller, Jürgen; Moll, Jens M.
Highlights: A variety of sgp130Fc muteins was generated. Introduction of a gp130 SNP (R281Q) into sgp130Fc increases IL-6 specificity. The sgp130Fc variant sgp130 FlyR exclusively affects IL-6 trans-signaling. Abstract: gp130 is the signal-transducing receptor for the Interleukin (IL)-6 type cytokines IL-6 and IL-11. To induce signaling, IL-6 forms a complex with IL-6 receptor (IL-6R) and IL-11 with IL-11 receptor (IL-11R). Membrane-bound IL-6R and IL-11R in complex with gp130 and the cytokine mediate classic-signaling, whereas trans-signaling needs soluble IL-6R and IL-11R variants. Interleukin (IL)-6 trans-signaling is of particular importance because it drives the development of autoimmune diseases, including rheumatoid arthritis and chronic inflammatory bowel diseases, whereas a role for IL-11 trans-signaling remains elusive. Soluble gp130 selectively inhibits trans-signaling of IL-6 whereas both, classic- and trans-signaling are abrogated by IL-6- and IL-6R-antibodies. Recently, we described an optimized sgp130 variant, which carries three amino acid substitutions T102Y/Q113F/N114L (sgp130 Fly Fc) resulting in reduced inhibition of IL-11 trans-signaling by increasing the affinity of sgp130 for the site I of IL-6. Moreover, we described that the patient mutation R281Q in gp130 results in reduced IL-11 signaling. Here, we show that the combination of T102Y /Q113F /N114L and R281Q in the new variant sgp130 FlyR Fc results in complete preservation of IL-11 mediated trans-signaling, whereas inhibition of IL-6 trans-signaling is maintained. Since sgp130Fc (olamkicept) has successfully completed a phase IIa trial in Crohn's disease (CD) and ulcerative colitis, sgp130 FlyR Fc might serve as second-generation therapeutic to diminish IL-11 trans -signaling cross-reactivity.